The contribution of media consumption in the political education of young people as part of their citizen training: Comparative study between areas of knowledge of higher education in Mexico - Leyva Cordero, Oswaldo; Tamez González, Gerardo; Ganga Contreras, Francisco; Marañón Lazcano, Felipe de Jesús (Ponte, Florence Italy, 2017)
One of the challenges the Mexican education system faces is the building of capacities to foster civic and political participation in young people, a fundamental task in citizen formation. In such a way that political education promotes the transformation of individuals to develop comprehensive thinking skills, which generates the exercise of a full and active society. Sotirovic and McLeod (2004) approach the perspective of political socialization as a process of community learning, through which citizens acquire beliefs, feelings and information for the purpose of achieving maturity and political identity. This system addresses exposure to the media and its effects on the individual, that is, cognitive ones such as consciousness, knowledge and the image of politicians; the affective ones like interests, attitudes towards leaders, subjects and attachment to the political system; and, finally, those of behavior as interpersonal discussion and political participation. In that sense, a comparative analysis of the six areas of knowledge established by the National Institute of Statistics and Geography (INEGI, 2014) is established, with the objective of evaluating the political learning of young people, which is strengthened through media consumption and its link with democratic participation, because it is considered a relevant context of vulnerability in civic and political life.